The Challenges and Prospects of Oil Companies Activities on Communities in Akwa Ibom State, Nigeria (Global Journal of Human-Social Science, 2012)
The rising issues is what has happened to the impoverished communities in Eket Local Government Area whose livelihoods have been affected due to the activities of oil companies which is the backdrop of this work However Two communities were used namely Mkpanak and Upenekang of which ninety three copies of questionnaire were randomly distributed to each of the community in order to captured the impact of the oil companies activities such as type of infrastructural development impact on the environment nature of activities and companies by-products The data collected were analyzed using the Pearson s product moment correlation However Findings show that even though the oil companies in the area have contributed significantly to the socio-economic wellbeing of the people through income generation employment creation provision of social amenities their activities were not devoid of environment crises These crises arises due to oil spills which in turn affect the soil nutrients lost of aquatic life and mangroves Beside the data analyzed show a high positive relationship between the companies by-product and the impact on the environment which indicate that the oil companies have really destroyed the natural ecosystem which is the major source of sustenance to the impoverished communities Therefore the various stakeholders in environmental management must provide a mechanism that would guarantee the sustainability of the people in the ecosystem
Keywords: Aquatic life; Devastated; Ecosystem; Environment; oil companies